Numerical Finite Difference Method of Electric Field Generated to Determine the Sar Generated in a Microstrip Antenna Type Applied to a Wban - Kaschel-Carcamo, H; Lanyon-Olivares, C (IEEE Computer Society, 2016)
This paper gives an alternative method to determine the Specific Absorption Rate (SAR), amount of electromagnetic energy absorbed by the human body, using the numerical finite difference method with MATLAB software, from the electric fields generated by a type patch antenna applied to a Wireless Body Sensor Network (WBAN). These networks consist of bodily wireless sensors distributed inside or outside the human body for measuring physiological parameters. The research begins by defining electrical characteristics within the human body, to finally present and calculate the specific absorption rate SAR. © 2016 IEEE.